Stem Cell Therapy: Advancements, Applications, and Future Prospects in Regenerative Medicine - Nidhi K. Parmar*; Beauty A. Yadav; Krinal A. Patel; Disha J. Nagdev; Bisojeet R. Khandai (International Journal of Cell Biology and Cellular Functions, 2026)
Stem cell therapy has come up as a revolutionary technique in regenerative medicine living up to the promise in treating numerous diseases and injuries. The latest discoveries made in the field of stem cell research such as the introduction of gene editing technology like CRISPR and the creation of the 3D bioprinting process have increased the accuracy and efficacy of stem cell-based therapies. Examples include cardiac regeneration and repair of the nervous system, and degenerative conditions, including Parkinson and osteoarthritis. Moreover, personalized medicine and induced pluripotent stem cells (iPSCs) are setting the stage of patient-specific treatment with the lowest chance of immune rejection. But obstacles like ethical issues, risk of safety, and regulation are still there. In the future, stem cell therapy promises to be very useful in cancer treatment, and tissue engineering. Further research and innovation are likely to address such challenges and eventually transform the treatment process of complex diseases and patient outcomes.
Keywords: 3D bioprinting; CRISPR; Personalized medicine; Stem cell therapy; cancer treatment; induced pluripotent stem cells; regenerative medicine; tissue engineering